1992
DOI: 10.1073/pnas.89.8.3443
|View full text |Cite
|
Sign up to set email alerts
|

A viral protease-mediated cleavage of the transmembrane glycoprotein of Mason-Pfizer monkey virus can be suppressed by mutations within the matrix protein.

Abstract: The envelope glycoprotein precursor of retroviruses undergoes proteolytic cleavage in the Golgi complex to yield the mature surface and transmembrane (TM) glycoproteins of the virus. We report here that the TM glycoprotein of Mason-Pfizer monkey virus undergoes a second proteolytic processing event during a late maturation step that can follow virus release and Gag polyprotein cleavage. Cleavage results in the conversion of the cell-associated TM glycoprotein (gp22) to a virus-associated gp2O. Processing conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
52
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 36 publications
4
52
0
Order By: Relevance
“…The TM glycoprotein also mediates virus-cell membrane fusion during viral entry as well as cell-cell fusion via a fusion peptide and heptad repeat motifs located at the extracellular domain (2,18,35,69,74,76). This fusion process also is influenced by the cytoplasmic domain of the TM glycoprotein as demonstrated previously (9,13,19,36,44,55,68,70).As is observed with murine leukemia virus (MuLV) and Gibbon ape leukemia virus, but unlike most other retroviruses, a viral protease-mediated maturational cleavage of the TM cytoplasmic domain occurs following virus release, which results in conversion of gp22 into gp20 (9,10,13,55,67). Based on cytoplasmic domain truncation mutants, this maturational cleavage of the cytoplasmic domain appears to dramatically increase the fusion activity of the TM proteins and results in the loss of 17 amino acids from the carboxy terminus of the cytoplasmic domain (9, 68).…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…The TM glycoprotein also mediates virus-cell membrane fusion during viral entry as well as cell-cell fusion via a fusion peptide and heptad repeat motifs located at the extracellular domain (2,18,35,69,74,76). This fusion process also is influenced by the cytoplasmic domain of the TM glycoprotein as demonstrated previously (9,13,19,36,44,55,68,70).As is observed with murine leukemia virus (MuLV) and Gibbon ape leukemia virus, but unlike most other retroviruses, a viral protease-mediated maturational cleavage of the TM cytoplasmic domain occurs following virus release, which results in conversion of gp22 into gp20 (9,10,13,55,67). Based on cytoplasmic domain truncation mutants, this maturational cleavage of the cytoplasmic domain appears to dramatically increase the fusion activity of the TM proteins and results in the loss of 17 amino acids from the carboxy terminus of the cytoplasmic domain (9, 68).…”
mentioning
confidence: 70%
“…It is then cleaved by a cellular protease into two subunits, gp70 (SU) and gp22 (TM), in a late compartment of the Golgi complex (26). The oligomeric, noncovalently associated gp70 and gp22 complexes are then transported to the plasma membrane, where they are incorporated into budding virions (10,68). The SU glycoprotein is responsible for receptor binding, whereas the TM glycoprotein is responsible for anchoring the SU protein at the surface of infected cells or the viral membrane.…”
mentioning
confidence: 99%
“…It has been suggested that the virus has adopted this strategy of regulating Env fusogenicity in order to limit the expression of a potentially cytotoxic molecule on the cell surface (53,54). Similar processing of Env cytoplasmic tails has been observed in the MasonPfizer monkey virus (M-PMV), the gibbon ape leukemia virus (GaLV), and the equine infectious anemia virus (4,7,56); in addition, truncated M-PMV and GaLV Env proteins are more fusogenic than their full-length counterparts (3,7). Truncations of the long cytoplasmic domains of lentiviral Env proteins occur under certain culture conditions (5,31,32,59), and an increase in Env fusogenicity has been reported for truncated versions of simian immunodeficiency virus (SIV), human immunodeficiency virus type 1 (HIV-1), and HIV-2 Envs (18,45,63,64,68,80).…”
mentioning
confidence: 84%
“…Several viral proteins are known to be cleaved inside retroviral virions by PR, such as HIV-1 Vif (35), HIV-1 and HIV-2 Nef (4,43,50,54), and, in several retroviruses, the cytoplasmic tail of the transmembrane portion of Env (2,19,23). However, up to this point, it has not been generally agreed that Gag proteins can be cleaved in budded virus, with the exception of the CA-p2 intermediate of Rous sarcoma virus Gag (1).…”
Section: Discussionmentioning
confidence: 99%